Front Cover: Deciphering Specificity Determinants for FR900359‐Derived Gqα Inhibitors Based on Computational and Structure–Activity Studies (ChemMedChem 16/2018). (21st August 2018) - Reher, Raphael; Kühl, Toni; Annala, Suvi; Benkel, Tobias; Kaufmann, Desireé; Nubbemeyer, Britta; Odhiambo, Justin Patrick; Heimer, Pascal; Bäuml, Charlotte Anneke; Kehraus, Stefan; Crüsemann, Max; Kostenis, Evi; et al.
Abstract : The Front Cover shows the depsipeptide FR900359 which can be isolated from the traditional Chinese medicine plant Ardisia crenata . It represents, together with the related YM254890, the most efficient compound to inhibit the activity of the Gq α protein so far. Investigations revealed that also among a set of approximately 40 known natural and synthetic analogs, FR900359 still represents the gold standard to suppress Gq α‐mediated signaling. The design and production of FR‐analogs with an improved efficiency, while addressing the same binding site, is nearly impossible for both, the semisynthetic modification of natural isolated compounds as well as the synthetic production, since the majority of the structure of FR cannot be changed without a significant loss of activity. Thus, FR900359 is regarded as the pharmacophore for binding to and inhibition of Gq α. More information can be found in the Full Paper by Daniel Tietze, Gabriele M. König, Diana Imhof et al. onpage 1634 in Issue 16, 2018 (DOI:10.1002/cmdc.201800304 ).